Co-design of event generator and quantized fault detection for time-delayed networked systems with sensor saturations. Issue 15 (October 2017) - Tan, Yushun; Du, Dongsheng; Fei, Shumin
Abstract: This paper investigates the problem of fault detection for the time-delayed networked systems. Different from the traditional fault detection systems, the considered system has the following feature: (i) the measured output of system is subject to sensor saturations; (ii) the system considers the influence of transmission delay and disturbance, which are two common phenomenon under the network environment; (iii) an output-dependent triggered scheme and measurement quantization are introduced in order to reduce the network bandwidth burden and improve communication efficiency. Considering aforementioned characteristics, a new type of fault detection filter model is builded. By constructing a Lyapunov functional, some new sufficient conditions for both the existence of above filter and the mean square stability of networked systems are obtained in terms of linear matrix inequalities (LMIs). Moreover, the suitable fault detection filter and the event generator can be co-designed simultaneously. Finally, a simulation example and an industrial continuous stirred tank reactor system are employed to verify the effectiveness and usefulness of the proposed method.